Human health risk assessment of toxic elements in soils and crops around Xiaoqinling gold-mining area, Northwestern China. Issue 2 (March 2023) - Yang, Min; Zhang, Jianghua; Chen, Huaqing; Ke, Hailing; Xu, Youning
The threat to the quality and safety of agricultural products from toxic elemental pollution is a critical contemporary problem. Extensive mining and lax management in the Xiaoqinling gold-mining area from 1986 to 2000 have increased the toxic element concentrations in soils, groundwater, and crops around the mines. Long-term excessive intake of Hg, Pb, Cd, Cr, Cu, and Zn can cause serious life-threatening human diseases, such as hydromelalgia, lead poisoning, Itai Itai disease, chronic rhinopathy, and acute hemolysis. Influenced by local environmental conditions, toxic elements in soils and crops enter the food chain and endanger human health. To determine the health risks from toxic elements introduced by mineral exploitation in Xiaoqinling, soil, wheat, and corn samples were analyzed for Hg, Pb, Cd, Cr, As, Cu, and Zn content. The contamination risks of toxic elements in soils were assessed using the single pollution index and risk assessment code method. The human health risks from toxic elements through wheat and corn consumption were evaluated using transfer factor (TF) and hazard quotient (HQ). The results indicated severe Hg, Pb, Cd, Cu, and Zn accumulation in the mining-affected soils. The TF revealed a relatively easier transformation of Cd, Zn, and Cu from soil to crops, and the HQ showed a high risk of Pb intake from wheat and corn.